Pembelajaran Matematika Berbasis Video Dalam Mengembangkan Motivasi Dan Minat Belajar Siswa Kelas II Sekolah Dasar Negeri 2 Jatipuro Kabupaten Klaten - Eka Zahra, Imroatun; Marhamatus Saadah; Ariska Mawar; Nela Rofisian (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
The research was carried out because of problems related to the lack of student learning outcomes in mathematics learning, due to the large number of students who experienced obstacles in learning mathematics. The purpose of this study is to find out the results of mathematics learning of students before and after using learning media using video media in grade II students of SD Negeri Jatipuro Klaten and to determine the influence of mathematics learning outcomes of students who use video-based learning media in grade II students of SD Negeri Jatipuro Klaten 2. The research methods used are literature studies, interviews, and observations. The interest in learning mathematics in students before there was a video learning media for grade II of SD Negeri 2 Jatipuro Klaten was still very low and there was a lack of motivation from educators, while the interest in learning mathematics of students after using learning videos in grade II students of SD Negeri 2 Jatipuro Klaten experienced a very good increase for students and there was an important influence on students' interest in learning mathematics using learning video media for participants Grade II student at SD Negeri 2 Jatipuro Klaten. With this, learning video media can be used for learning purposes.